Apocalypse Now: Dombey in the Twenty-First Century - Jennifer Gribble (Cahiers Victoriens et Edouardiens)
The narrative injunction to Mr Dombey, ‘awake, doomed man,’ has a Carlylean, Miltonic and biblical source, but it also strikes a significant key-note for early twenty-first-century readers. Acts of unimaginable terror, catastrophic natural disasters and a global sense of humankind’s time running out might make us particularly receptive to the apocalyptic tone and message of Dombey and Son. And renewed currency is being given to the Victorian debate about God, pursued in this novel’s remorselessly ticking clocks and watches, weighing railway time against the end-time of 1840s millenarianism and the timelessness of eternity. Contemporary readers are, however, disinclined and often unable to consider Dickens’s purposeful biblical intertextuality, despite the widespread reading practices of New Historicism and Discourse Analysis. This paper argues that the Judeo-Christian grand narrative is fundamental to the narrative structure, thematics and ethical arguments of Dombey and Son, and that it actively engages with other influential narratives in the topical public sphere. In a progressive unfolding of the great scroll, from Genesis, the law, the prophets and the Psalms, through the Sermon on the Mount to the Book of Revelation, Dickens reads the signs of his times in the light of the biblical time-line from Creation to Apocalypse. Dombey’s pride has theological as well as economic implications: his sense of lordship over nature is representative of the technological, commercial and scientific advances of an expanding empire. Transcending simplifying providential and romance plots, the novel’s focus on the urgent personal and philosophical question of ‘what nature is’ draws on the insights of Romanticism to probe the relationship between the observable universe of nature’s laws and belief in a divinely-activated universe of meaningful pattern and revelation.